Exploring potential applications of measles and rubella microarray patches (MR-MAPs): use case identification - Malvolti, Stefano; Ko, Melissa; Menozzi-Arnaud, Marion; Mantel, Carsten; Jarrahian, Courtney; Amorij, Jean-Pierre; Giersing, Birgitte; Hasso-Agopsowicz, Mateusz (Frontiers in Public Health, 2023)
Introduction Innovative vaccine products will be critical in helping to address the existing implementation barriers that have prevented the achievement of the measles and rubella (MR) vaccine coverage targets. Overcoming those barriers will be necessary to achieve the “Immunization Agenda 2030” goals. Microarray patches (MAPs), an innovative needle-free delivery device currently in clinical development, can be a potential game changer in this respect and contribute to the equitable delivery of vaccines in low- and middle-income countries and pandemic preparedness and response. Developing in-depth knowledge of the most desired and impactful uses of MRMAPs can prove critical to identifying the critical attributes of the target product profile, informing policy and adoption decisions, and helping to evaluate the potential public health and economic value of this technology. The first step in this process is the definition of the potential use cases for MR-MAPs, i.e., where and how this product is most likely to be used within the immunization programme. Methods By applying a design-based user-centric approach, we implemented a three-step process, including a desk review, a survey, and interviews, to define the most relevant use cases for MR MAPS. Results Six use cases have been identified as relevant across all different countries and immunization programme designs and validated by experts. Discussion The identified use cases have already informed the demand estimate for MR-MAPs and provided the foundation for developing an initial full vaccine value assessment. We believe that, in the future, they will be highly valuable in ensuring that the roll-out of this promising innovation is designed in a way that maximizes the impact, particularly in populations and countries that are most in need.